Gaussian plume models and "cloud" computing for 3d analysis of the state atmosphere - Воробець, Георгій Іванович; Скрипський, Микола Ігорович (Eastern-European Journal of Enterprise Technologies, 2013)
The proposed method and developed software for a three-dimensional simulation of the spread of contaminants in the atmosphere using the Gaussian dispersion models, "cloud" technologies and software OpenMP allows improving the efficiency of using computing resources. It is achieved by developing a common approach to improving the problem definition of simulation modeling and data preparation. According to the testing results, the developed program module accelerates computations by 4 times compared to the single-processor system and allows constructing the map of the contaminants spread using the Gaussian dispersion models. The obtained results prove the feasibility of using the OpenMP software package for the parallelization of computations and indicate the possibility of further software optimization for solving this class of problems according to the criterion of minimizing the computing time by varying the number of parallel threads, processes and involved processor cores.